Correlation between transverse and vertical measurements in Brazilian growing patients, evaluated by Ricketts-Faltin frontal analysis - Regina Helena Lourenço Belluzzo; Kurt Faltin Jr; Cristina Ortolani; Adolpho Chelotti (Dental Press Editora, 2013)
INTRODUCTION: Currently in orthodontic diagnosis, besides the lateral cephalometric analysis which evaluates the anteroposterior and vertical direction, the frontal analysis may be added, leading us to another important dimension in space: the transverse dimension. OBJECTIVE: Few longitudinal samples with the frontal radiograph were published, so this cephalometric study was designed to correlate the transversal and vertical measures by Ricketts-Faltin frontal analysis into two radiographic times. METHODS: The sample consisted of 45 Brazilian children, 25 girls and 20 boys, all presenting mixed dentition, with balanced facial aesthetics and no previous orthodontic/orthopedic treatment. The initial average age (T1) was 7.7 years and the final (T2) 13.3 years. The measurements evaluated were: FTD, MxTD, NTD, LITD, MdTD (transversal), OVD and TVD (vertical). RESULTS: All transversal measures were positively correlated with a medium or high correlation with each other and the vertical measurements; only LITD presented a low correlation with these measurements. CONCLUSION: It was concluded that the face has interdependent regions and that this feature remains with growth. INTRODUÇÃO: atualmente no diagnóstico ortodôntico, além da análise cefalométrica lateral - que avalia os sentidos anteroposterior e vertical -, deve-se acrescentar a análise no sentido frontal, a qual propicia outra dimensão importante no espaço, a transversal. OBJETIVO: poucas são as amostras longitudinais publicadas utilizando telerradiografias frontais; portanto, o presente estudo cefalométrico teve o intuito de correlacionar as medidas transversais e verticais por meio da análise frontal de Ricketts-Faltin, em dois tempos radiográficos. MÉTODOS: a amostra constou de 45 crianças brasileiras, sendo 25 meninas e 20 meninos, todos apresentando dentição mista, com perfil harmonioso e sem nunca terem sido tratadas ortodonticamente e/ou ortopedicamente. A idade média inicial (T1) foi de 7,7 anos e a final (T2) de 13,3 anos. As medidas avaliadas foram: DTF, DTMx, DTN, DTII e DTMd (transversais); DVO e DVT (verticais). RESULTADOS: todas as medidas transversais estavam correlacionadas positivamente, em grau médio ou forte, entre si e com as medidas verticais; somente DTII estava correlacionada em grau fraco com essas medidas. CONCLUSÃO: concluiu-se que a face possui regiões interdependentes, e assim mantém-se mesmo com o crescimento.